Biosorption of Lead, Cadmium, and Zinc onto Sunflower Shell: Equilibrium, Kinetic, and Thermodynamic Studies - Mohammed, Ahmed A. (Iraqi Journal of Chemical and Petroleum Engineering, 2015)
The present study deals with the application of an a bundant low cost biosorbent sunflower shell for metal ions removal. Lead, Cadmium and Zinc were chosen as model sorbates. The influences of initial pH, sorbent dosage, contact time, temperature and initial metal ions concentration on the removal efficiency were examined. The single ion equilibrium sorption data were fitted to the non-competitive Langmuir and Freundlich isotherm models. The Freundlich model represents the equilibrium data better than the Langmuir model. In single, binary and ternary component systems,Pb+2 ions was the most favorable component rather than Cd+2 and Zn+2 ions. The biosorption kinetics for the three metal ions followed the pseudo-second order kinetics indicating that the chemical sorption was the rate-limiting step. The thermodynamic parameters including free energy ( G0), enthalpy and entropy changes for Pb2+,Cd2+ and Zn2+ ions indicated that the sorption process was feasible,spontaneous,and endothermic in the temperature range 20-50 0 C .Desorption of the three metals ions from the biosorbent was effectively achieved in a  0.2 mol L-1 HCl solution.